Government by the people. - Magleby, David B. (Pearson/Prentice Hall, 2008)
"Discusses the make-up and function of the U.S. system of government. Its primary focus is on the modern political system in the United States. This focus centers on how the federal and state governments are constructed and the comparative political ideologies that influence how those governments operate"--Provided by publisher.